Molecular characterization and isoenzyme profiles of giardia duodenalis isolates from Iranian patients in Fars Province, Iran - Rayani, Mohammad (2014)
Giardia duodenalis is the most common intestinal parasite among humans and is endemic throughout the world. Diarrhea and malnutrition are the main clinical pathogenesis especially in children. Giardiasis is one of the common infections found occurring in Iran. Identifying the prevalence of the common genotype assemblages and zymodemes of G. duodenalis in this province will allow for a better understanding of the route and source of the transmission for G.duodenalis, especially related to the control and prevention strategies. The heterogeneity among G. duodenalis strains may explain the variable clinical manifestations, host response and treatment efficacy characteristic of human giardiasis. The first objective was to study the genetic characterization of G. duodenalis isolates at Fars Province, south of Iran by semi-nested PCR and isoenzyme analyses. The second objective was to identify the most common G. duodenalis assemblages or sub-assemblages involved in the transmission of giardiasis in this area. Human fecal samples (n=1000) were collected from health centers and hospitals in Fars province, south of Iran from September 2009 to August 2010. Standard fecal staining method and microscopic confirmation of both G. duodenalis cysts and trophozoites were performed before and after the fecal concentration method. Purification and isolation of G. duodenalis cysts and trophozoites were based on the modification of the standard sucrose gradient method. Consequently, DNA was extracted using the standard Phenol Chloroform Isoamyl Alcohol method. A fragment of the SSU-rDNA (292 bp) gene was amplified using the forward primer RH11 and reverse primer RH4. Semi-nested PCR and sequence analysis were then performed using primers GDHeF,GDHiF, and GDHiR that amplifies a 432 bp fragment of the glutamate dehydrogenase gene (gdh). Phylogenetic analysis was carried out using a neighbor-joining tree composed of the 40 nucleotide sequences of successfully isolated G. duodenalis and compared with the known sequences published in GenBank. Fifteen cultures of G. duodenalis isolates were analyzed using isoenzyme in a polyacrylamide gel electrophoresis (PAGE). Five different enzyme systems were used to characterize each isolate: (i) Glucose-6-phosphate dehydrogenase (G6PD, E.C.1.1.1.444), (ii) Glucose phosphate isomerase (GPI, E.C. 5.3.1.9), (iii) Malate dehydrogenase (MDH, E.C. 1.1.1.37), (iv) Malic enzyme (ME, E.C. 1.1.1.40) and (v) Phosphoglucomutase (PGM, E.C. 2.7.5.1). The results indicated that 107/1000 (10.7%) samples were found positive for G. duodenalis based on microscopy confirmation. Almost similar results were observed in molecular study and isoenzyme profile analysis. PCR analysis identified 80% (40/50) samples were positive for G. duodenalis based on SSU-rDNA amplification on sucrose gradient samples. Further genotyping has resulted in 80% (32/40 samples) isolates as sub-assemblage of AII and 20% (8/40 samples) isolates as assemblage B based on the DNA sequence of the gdh. Phylogenetic analysis had shown that G. duodenalis isolates at Fars province were widely distributed within assemblage A cluster (sub-assemblage AII) and the remaining isolates were dispersed throughout the assemblage B cluster (sub-assemblage BIII and BIV). Electrophoretic heterogeneity was found in G. duodenalis enzymes profile. One identical isozyme was detected for G6PD isoenzyme pattern. Two different isozymes were detected for GPI and MDH isoenzyme patterns. In addition, three different isozymes were detected for ME and PGM isoenzyme patterns. Further analysis has shown that four zymodemes were found among the fifteen isolates of G. duodenalis. The zymodemes 1, 2, 3 and 4 was observed to have similarity with 7, 2, 4 and 2 isolates, respectively. In conclusion, five isoenzyme systems were used in this study; these are G6PD, GPI, MDH, ME and PGM for the characterization of G. duodenalis isolates and distinguish zymodemes of the parasite in Iran. The isoenzyme electrophoretic profiles divided fifteen G. duodenalis isolates into four zymodemes and revealed genetic heterogeneity between the Iranian isolates. These variations are related to the clinical manifestation, pathogenicity, drug susceptibility and host specificity. G6PD isoenzyme pattern had the most homogeneity, while ME and PGM isoenzyme pattern had the most heterogeneity in our study. The present study showed that G. duodenalis sub-assemblage AII was the predominant assemblage in Fars Province. This indicates an anthroponotic transmission from human to human was one of the main causes of giardiasis in this area. Health promotion, public education, improving sanitation conditions, personal hygiene, improving clean drinking water and food are important strategies that should be addressed to control and prevent giardiasis. Through this study, potentially important and useful data on the distribution of different genotypes and isoenzymes profiles of G. duodenalis in Iran were obtained. These data represent a significant advancement in the current understanding of the transmission of G. duodenalis assemblages in Iran and could aid in future studies for epidemiology, clinical management and prevention purposes.